Reading interests of Pegawai Negeri officers in Indonesian Civil Service in the Philippines - Suharyono, Toettie S. (Institute of Library Science, University of the Philippines Diliman, 1994)
The reading interests of the Pegawai Negeri officers and staff of the Indonesian Civil Service in the Philippines was the subject of this study. They are assigned at the Indonesian Embassy in Manila and the Consulate General in Davao City. Sixty out of 120 respondents comprise the respondents of the study. The aims of the study are to 1) find out what the Pegawai Negeri officers read; 2) identify the subjects and types of materials they read; 3) identify the sources of materials they read; 4) identify the language preference for materials they read; and 5) identify the factors that influence their reading interest.